SOI photonic crystal waveguides operating in telecommunication range for integrated circuits - Cam, Hoang Thi Hong; Anh, Trinh Duc; Binh, Pham Thanh; Dai, Pham Van; Van, Nguyen Thuy; Hoi, Pham Van (Vietnam Journal of Science and Technology, 2020)
Silicon photonics has been of great interest and plays an significant role in optical communications. Various devices acting as the key components of integrated circuits can be generated based on silicon-on-insulator (SOI) platform. Among those, SOI photonic crystal waveguide (SOI PCW) have been considered as one of the most fundamental and essential elements. In this report, we present the design and the numerical property of SOI PCWs operating in telecommunication range, i.e., O-band (1260 – 1360 nm)with TE and/or TM polarizations. The SOI PCWsincluding conventional W1 and slot SOI PCWs have been designed in order to exploit two kinds of mode: W1-like and true-slot.For that purpose, the geometric parameters of the SOI PCW withthe triangular PhC structure are chosen as follows. The thickness of the silicon slab was fixed at 300 nm to match with the fabrication in industrial scale, the size of the hole was around 210 nm and the lattice constant was tuned in the range of 300 nm to 400 nm. The width of waveguide was modified fromW1 to W1.50 and the width of the slot was of about 100 nm. In addition,the covering materials were selected with refractive index of 1.0 corresponding to air as well as refractive indices of from 1.45 to 1.50 corresponding to the active materials. The demonstrated SOI PCWs in this work might find applications in optical integrated circuits and our investigation on the dependence of the dispersion on the width of waveguide and refractive index of the covering material will provide a general guide line for guiding signal and for monitoring or sensing purposes…